First report of the Pineapple mealybug wilt-associated viruses 1, 2 and 3 causing pineapple mealybug wilt disease in East Malaysia, Borneo - Mohammed, M. A.; Aman‐Zuki, A.; Buang, M. G.; Abu Bakar, F.; Sartiami, D.; King, P. J. H.; Yaakop, S. (John Wiley and Sons, 2024)
Mealybug wilt of pineapple (MWP) is associated with three pineapple mealybug wilt-associated viruses (PMWaVs) which negatively impact crop production globally (Dey et al., 2018). MWP symptoms include wilting, marginal leaf curl, reddish-yellow colouration of the leaves beginning at the tip, and a desiccated appearance of the plants (Dey et al., 2018). Pineapple farmers in Sarawak, Borneo have consistently reported the widespread occurrence of MWP symptoms since 2021 (Figure 1). The roots and fruit of diseased plants were observed to be infested with mealybugs. Three samples of diseased pineapple leaves, mainly of the cvs. Josapine, MD2, Morris and Sawit, were gathered from each of four different pineapple plantations in Bintulu, Miri, Sibu and Kuching, in the north, centre and south of Sarawak between 2021 and 2022. The pineapple leaves were pooled according to their localities, sliced into pieces 1 × 2cm, preserved in RNAlater (Thermo Fisher, USA) and then transported to the laboratory. RNA was extracted from the leaves using the SEPa Plant Isolation Reagent Kit (1st BASE, Singapore) according to the manufacturer's guidelines. A two-step RT-PCR was performed to amplify the heat shock protein 70h gene of PMWaV-1, -2, and -3 (Green et al., 2020). PCR products of the expected size were Sanger sequenced (Apical Scientific Sdn. Bhd., Selangor) and the sequences were deposited in GenBank (Table 1). BLASTn analysis confirmed detection of PMWaV-1, -2, and -3 in each of the 12 samples. The percentage nucleotide identities of PMWaV-1, PMWaV-2 and PMWaV-3 with other isolates of each species ranged from 99.1-99.8, 99.6-100.0 and 98.4-99.8%, respectively (Table 1)